2018
DOI: 10.1007/s12410-018-9456-2
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Assessment with Cardiac CT: Ischemic Heart Disease and Beyond

Abstract: Purpose of ReviewThe aim of this review is to highlight recent advancements, current trends, and the expanding role for cardiac CT (CCT) in the evaluation of ischemic heart disease, nonischemic cardiomyopathies, and some specific congenital myocardial disease states.Recent FindingsCCT is a highly versatile imaging modality for the assessment of numerous cardiovascular disease states. Coronary CT angiography (CCTA) is now a well-established first-line imaging modality for the exclusion of significant coronary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 116 publications
1
12
0
Order By: Relevance
“…However, CCTA and CMRI generated more details for differential diagnosis. Previous studies have shown that CCTA, a noninvasive approach, can effectively distinguish outpouchings caused by myocardial infarction and ischemic cardiomyopathy related to occlusion (or lack thereof) of the coronary arteries[ 7 , 8 ]. Furthermore, CMRI has a unique advantage in identifying cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…However, CCTA and CMRI generated more details for differential diagnosis. Previous studies have shown that CCTA, a noninvasive approach, can effectively distinguish outpouchings caused by myocardial infarction and ischemic cardiomyopathy related to occlusion (or lack thereof) of the coronary arteries[ 7 , 8 ]. Furthermore, CMRI has a unique advantage in identifying cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The primary usefulness of cardiac CT, specifically non-invasive CCTA, has been well known among patients with CAD symptoms [5]. CCTA has evolved as an emerging utility of assessment for CAD, which can evaluate the coronary wall and anatomy, thus allowing to differentiate the existence of obstructive and non-obstructive coronary plaques [6].…”
Section: Discussionmentioning
confidence: 99%
“…Budoff et al 55 e Assessment of Coronary Artery Disease by Cardiac Computed Tomography Leipsic et al 56 e SCCT guidelines for the interpretation and reporting of coronary CT angiography: a report of the Society of Cardiovascular Computed Tomography Guidelines Committee National Institute for Health and Care Excellence (NICE) guidelines 4 : Chest pain of recent onset: assessment and diagnosis Knuuti et al 3 2019 ESC Guidelines for the diagnosis and management of chronic coronary syndromes Structural Heart Disease Blanke et al 25 e Computed tomography imaging in the context of transcatheter aortic valve implantation (TAVI)/TAVR: An expert consensus document of the SCCT Leipsic et al 57 e ACR Appropriateness Criteria® Imaging for Transcatheter Aortic Valve Replacement Blanke et al 32 e Mitral Annular Evaluation with CT in the Context of Transcatheter Mitral Valve Replacement Buttan et al 58 e Evaluation of Valvular Disease by Cardiac Computed Tomography Assessment Rizvi et al 59 e Analysis of Ventricular Function by CT Ismail et al 28 e CT imaging for left atrial appendage closure: a review and pictorial essay Carr et al 29 e CT of Left Ventricular Assist Devices Korsholm et al 30 e Expert Recommendations on Cardiac Computed Tomography for Planning Transcatheter Left Atrial Appendage Occlusion Leipsic et al 27 61 e Myocardial Assessment with Cardiac CT: Ischemic Heart Disease and Beyond Schuijf et al 37 e Fractional flow reserve and myocardial perfusion by computed tomography: a guide to clinical application. Singh et al 62 The role of computed tomography myocardial perfusion imaging in clinical practice.…”
Section: Discussionmentioning
confidence: 99%